Migration behavior of landfill leachate contaminants through alternative composite liners - Varank, Gamze; Demir, Ahmet; Top, Selin; Sekman, Elif; Akkaya, Ebru; Yetilmezsoy, Kaan; Bilgili, M. Sinan (ELSEVIER, 2011)
Four identical pilot-scale landfill reactors with different alternative composite liners were simultaneously operated for a period of about 540 days to investigate and to simulate the migration behaviors of phenolic compounds (phenol, 2-CP, 2-MP, 3-MP, 4-MP, 2-NP, 4-NP, 2,4-DNP, 2,4-DCP, 2,6-DCP, 2,4,5-TCP, 2,4,6-TCP, 2,3,4,6-TeCP, PCP) and heavy metals (Pb, Cu, Zn, Cr, Cd, Ni) from landfill leachate to the groundwater. Alternative landfill liners of four reactors consist of R1: Compacted clay liner (10 cm + 10 cm, k = 10(-8) m/sn), R2: Geomembrane (2 mm HDPE) + compacted clay liner (10 cm + 10 cm, k = 10(-8) m/sn), R3: Geomembrane (2 mm HDPE) + compacted clay liner (10 cm, k = 10(-8) m/sn)+ bentonite liner (2 cm) + compacted clay liner (10 cm, k = 10(-8) m/sn), and R4: Geomembrane (2 mm HDPE) + compacted clay liner (10 cm, k = 10(-8) m/sn) + zeolite liner (2 cm) + compacted clay liner (10 cm, k = 10(-8) m/sn). Wastes representing Istanbul municipal solid wastes were disposed in the reactors. To represent bioreactor landfills, reactors were operated by leachate recirculation. To monitor and control anaerobic degradation in the reactors, variations of conventional parameters (pH, alkalinity, chloride, conductivity, COD, TOC, TKN, ammonia and alcaly metals) were also investigated in landfill leachate samples. The results of this study showed that about 35-50% of migration of organic contaminants (phenolic compounds) and 55-100% of migration of inorganic contaminants (heavy metals) to the model groundwater could be effectively reduced with the use of bentonite and zeolite materials in landfill liner systems. Although leachate contaminants can reach to the groundwater in trace concentrations, findings of this study concluded that the release of these compounds from landfill leachate to the groundwater may potentially be of an important environmental concern based on the experimental findings. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Landfill leachate; Contaminant transport; Phenolic compounds; Heavy metals; Zeolite; Bentonite; ANAEROBIC SLUDGE BLANKET; ORGANIC-COMPOUNDS; REDUCTIVE DECHLORINATION; GROUNDWATER QUALITY; HEAVY-METALS; WASTE-WATER; DEGRADATION; PHENOL; PENTACHLOROPHENOL; TRANSPORT; Environmental Sciences & Ecology